Pengaruh Model POGIL (Process Oriented Guided Inquiry Learning) Terhadap Keterampilan Berpikir Kreatif dan Pemahaman Konsep Siswa Pada Materi Redoks - Aprilian, Malisa; Muhali, Muhali; Dewi, Citra Ayu (Hydrogen: Jurnal Kependidikan Kimia, 2018)
This study aims to determine the effect of POGIL to creative thinking skilland conceptual understanding of students at senior high school. This researchform of quasi experimental was carried out by postest-only control groupdesign. Research conducted in SMAN1 Montong Gading using sample whichdetermined by saturated sampling technique, 24 number of XA class studentsas experiment class, and 24 number of XB class students as control class.Creative thinking skills data was collected by observation sheets andconceptual understanding data by reasoning multiple choices test. The resultsshowed that the average creative thinking skill of experimental class at the 1st,2nd, and 3rdmeeting was 64.388, 72.656, and 79.752.The mean of creativethinking skill of the control class at the 1st, 2nd, and 3rdmeeting was 59.765,67.447, and 73.476.The hypothesis test result of creative thinking skill datausing independent sample t-test it is known that significance value of t-countwas 0.040 < 0.05, and conceptual understaning data by paired sample t-test itis known that significance value of t-count was 0.000 < 0.05. So that, there isinfluence of POGIL model to student creative thinking skill and conceptualunderstanding.